An investigation on gas hydrate formation and slurry viscosity in the presence of wax crystals - Shi, Bo‐Hui; Chai, Shuai; Ding, Lin; Chen, Yu‐Chuan; Liu, Yang; Song, Shang‐Fei; Yao, Hai‐Yuan; Wu, Hai‐Hao; Wang, Wei; Gong, Jing (AIChE journal, 2018)
Clarifying the interaction effect between hydrate and wax is of great significance to guarantee operation safety in deep water petroleum fields. Experiments in a high‐pressure hydrate slurry rheological measurement system were carried out to investigate hydrate formation and slurry viscosity in the presence of wax crystals. Results indicate that the presence of wax crystals can prolong hydrate nucleation induction time, and its influence on hydrate growth depends on multiple factors. Higher stirring rate can obviously promote hydrate growth rate, while its influence on hydrate nucleation induction time is complicated. Higher initial pressure will promote hydrate formation. Gas hydrate slurry shows a shear‐thinning behavior, and slurry viscosity increases with the increase of wax content and initial pressure. A semiempirical viscosity model showing a well‐fitting is established for hydrate slurry with wax crystals by considering the aggregation and breakage of hydrate particles, wax crystals, and water droplets. © 2018 American Institute of Chemical Engineers AIChE J, 64: 3502–3518, 2018